Dampak Mediasi Komitmen Profesional Mempengaruhi Otonomi Kerja dan Kompetensi terhadap Job Engagement (Studi pada Pegawai Inspektorat Daerah Kabupaten Boven Digoel) - W.S. Agung Romadona (IPM2KPE, 2024)
This research aims to determine the mediating influence of professional commitment in influencing work autonomy and competence on work engagement. The method used is a quantitative method. The data analysis method used is Partial Least Square (PLS) analysis. The research results showed that the work autonomy variable obtained P values > 0.05 (0.324 > 0.05) and t-statistics < 1.96 (0.987 < 1.96). The competency variable has a P value > 0.05 (0.818 > 0.05) and t-statistic < 1.96 (0.231 < 1.96). This value shows that work autonomy and competence do not have a positive and significant effect on work engagement. This research also proves that work autonomy does not have a positive and significant effect on professional commitment because it has a P value > 0.05 (0.449 > 0.05) and t-statistic < 1.96 (0.758 < 1.96). Competence has a positive and significant effect on professional commitment because it has P Values < 0.05 (0.000 < 0.05) and t-statistics > 1.96 (24.086 > 1.96). Keywords: Job Engagement, Competence, Mediation of Professional Commitment